Corrosion electrochemical behavior of cadmium-plated 4340 steel in aircraft landing gears under thin electrolyte layers of potassium acetate deicing fluid. (28th August 2019) - Lin, Xiuzhou; Zhang, Runhua; Mei, Yongjun; Yang, Li; Yang, Feng; Dou, Baojie; Wei, Yongqiang
Abstract : We present a study of the corrosion behavior of cadmium-plated 4340 steel in aircraft landing gears under thin electrolyte layers of potassium acetate deicing fluid. Abstract : We present a study of the corrosion behavior of cadmium-plated 4340 steel in aircraft landing gears under thin electrolyte layers of potassium acetate deicing fluid. The corrosion rate was evaluated by electrochemical experiments and the results were compared with tests conducted under full immersion conditions in the deicing fluids. Scanning electron microscopy (SEM) was employed for the examination of the surface and cross-sectional morphologies of the cadmium-plated 4340 steel for different test conditions. The results from electrochemical experiments revealed that the corrosion rate was mainly controlled by the cathodic oxygen process and the test carried out under thin electrolyte layer conditions resulted in higher corrosion rate compared to that for the full immersion conditions. Results from SEM analysis were generally consistent with those from the electrochemical measurements.